A metabolomic study of cervical dystonia. (January 2021) - Liu, Chang; Scorr, Laura; Kilic-Berkmen, Gamze; Cotton, Adam; Factor, Stewart A.; Freeman, Alan; Tran, ViLinh; Liu, Ken; Uppal, Karan; Jones, Dean; Jinnah, H.A.; Sun, Yan V.
Abstract: Introduction: Cervical dystonia is the most common of the adult-onset focal dystonias. Most cases are idiopathic. The current view is that cervical dystonia may be caused by some combination of genetic and environmental factors. Genetic contributions have been studied extensively, but there are few studies of other factors. We conducted an exploratory metabolomics analysis of cervical dystonia to identify potentially abnormal metabolites or altered biological pathways. Methods: Plasma samples from 100 cases with idiopathic cervical dystonia and 100 controls were compared using liquid chromatography coupled with mass spectrometry-based metabolomics. Results: A total of 7346 metabolic features remained after quality control, and up to 289 demonstrated significant differences between cases and controls, depending on statistical criteria chosen. Pathway analysis revealed 9 biological processes to be significantly associated at p < 0.05, 5 pathways were related to carbohydrate metabolism, 3 pathways were related to lipid metabolism. Conclusion: This is the first large scale metabolomics study for any type of dystonia. The results may provide potential novel insights into the biology of cervical dystonia. Highlights: The first large-scale metabolomics study of cervical dystonia. Altered biological pathways may relate to carbohydrate and lipid metabolism. Novel insights into the disease mechanism of cervical dystonia.